2011
DOI: 10.1111/j.1439-0418.2011.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Varroa management in small bites

Abstract: Chelifers (Arachnida: Pseudoscorpionida), also known as pseudoscorpions, have been reported to be beneficial honeybee hive generalist pest predators for over 100 years and are occasionally noted by beekeepers in their hives. We collected chelifers within or closely associated with beehives in New Zealand. Under video observation conditions, they predated upon varroa mites while studiously ignoring bee larvae. Varroa mites reproduce at exponential rates during the spring season, and current chemical miticides r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Varroa mainly devastate colonies when Varroa population grows unchecked. Effective control measures do not necessarily need to completely eradicate the Varroa population [34], [35]. Further studies would need to monitor the effect of dsRNA treatment on Varroa population dynamics and long-term effect on honey bee colonies under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Varroa mainly devastate colonies when Varroa population grows unchecked. Effective control measures do not necessarily need to completely eradicate the Varroa population [34], [35]. Further studies would need to monitor the effect of dsRNA treatment on Varroa population dynamics and long-term effect on honey bee colonies under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Since we observed the pseudoscorpions attacked only live varroa mites in the timelapse images and in real-time observations, and ignored varroa that had died during the assay, we concluded that the detection of varroa DNA in this predator was derived from live varroa it had killed. As reported by Fagan et al (2012) for N. gracilis and by Schiffer (2013a) for C. cancroides, both species can predate on live varroa in situ, and thus potentially reduce the live population of varroa mites in honey bee hives. That these species contain venom glands (Weygoldt, 1969), and paralyze their prey, supports the contention they prey on live arthropods.…”
Section: Discussionmentioning
confidence: 76%
“…Donovan and Paul (2006) presented photographs of E. indicus eating varroa, but Thapa, Wongsiri, Lee, and Choi (2013) concluded that E. indicus associated with Apis cerana do not act as a biocontrol of varroa mites, instead preying on dead honey bees, bee larvae, and psocids. N. gracilis has been observed to consume varroa in situ and each capable of consuming 1-9 mites per day (Fagan et al, 2012). C. cancroides has also been shown to consume up to 9 varroa per day (Schiffer, 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…larvae, which have been shown to sustain chelifer populations under laboratory conditions (Weygoldt ; Wood and Gabbutt ; de Andrade and Gnaspini ; Fagan et al. ), or apterous (wingless) pea aphids ( Acyrthosiphon pisum), which were readily reared on bean plants and also reported to be consumed by chelifers (Smith ). The chelifers consumed most of the prey they were provided over a three‐day period, and consequently were fed three times a week, as in other studies aimed at rearing chelifers where cultures were fed two or three times weekly (de Andrade and Gnaspini ; Tizo‐Pedroso and Del‐Claro ).…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory studies have shown these species capable of consuming 1–9 Varroa mites per day each (Fagan et al. ).…”
Section: Introductionmentioning
confidence: 99%